Veritesting Tackles Path-Explosion Problem. - Sen, Koushik (Communications of the ACM, 2016)
An article on the Veritesting dynamic symbolic execution and path merging or static symbolic execution testing technique for automating software testing as a method of solving the "path explosion" problem is introduced.